2022
DOI: 10.1186/s12866-022-02492-3
|View full text |Cite
|
Sign up to set email alerts
|

Organic mulch can suppress litchi downy blight through modification of soil microbial community structure and functional potentials

Abstract: Background Organic mulch is an important management practice in agricultural production to improve soil quality, control crop pests and diseases and increase the biodiversity of soil microecosystem. However, the information about soil microbial diversity and composition in litchi plantation response to organic mulch and its attribution to litchi downy blight severity was limited. This study aimed to investigate the effect of organic mulch on litchi downy blight, and evaluate the biodiversity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…However, in the current study, Xanthobacteraceae was positively correlated with OC, and was enriched in FB1_BOF. This may be consistent with the results of Xu et al (2022) , who reported that Xanthobacteraceae significantly increased in response to organic mulch. Streptomyces , an important group of soil bacteria belonging to the actinomycetes family, are widely reported in the literature for their plant growth-promoting rhizobacteria potential ( Nassar et al, 2003 ; El-Tarabily, 2008 ).…”
Section: Discussionsupporting
confidence: 93%
“…However, in the current study, Xanthobacteraceae was positively correlated with OC, and was enriched in FB1_BOF. This may be consistent with the results of Xu et al (2022) , who reported that Xanthobacteraceae significantly increased in response to organic mulch. Streptomyces , an important group of soil bacteria belonging to the actinomycetes family, are widely reported in the literature for their plant growth-promoting rhizobacteria potential ( Nassar et al, 2003 ; El-Tarabily, 2008 ).…”
Section: Discussionsupporting
confidence: 93%
“…Ramirez et al reported that organic mulch suppresses avocado infection by Phythophthora cinnamoni [31]. In comparison, Xu et al said that mulch suppresses litchi downy blight caused by Peronophythora litchii by increasing the diversity of soil microbial communities [32]. A similar study by Zhang et al showed that organic mulch increased the diversity of soil microbes such as groups of bacteria Proteobacteria, Actinobacteria, Acidobacteria, and Chloroflex and groups of fungi Ascomycota, Mortierellomycota and Basidiomycota became dominant [33].…”
Section: Resultsmentioning
confidence: 98%
“…In this study, the relative abundances of K-strategists were significantly and positively correlated with soil nutrient contents, while the relative abundances of r-strategists had a negative relationship with soil nutrient availability. Acidobacteria is considered to have extensive metabolic and genetic functions [ 34 ]. Jiang et al [ 16 ] pointed out that Acidobacteria had numerous subdivisions, and different subdivisions showed varied correlations with soil nutrients.…”
Section: Discussionmentioning
confidence: 99%